2015
DOI: 10.1108/ijwbr-10-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Perceived efficacy of sustainability strategies in the US, Italian, and Spanish wine industries

Abstract: Purpose\ud – This purpose of this investigation is to compare the perceptions of competitive advantage through cost leadership and differentiation with sustainable practices of wineries from the USA, Italy and Spain.\ud \ud Design/methodology/approach\ud – Data are collected via self-report web-based surveys in California, Tuscany and Catalonia in 2010-2011 during a severe economic downturn in the wine industry.\ud \ud Findings\ud – Of the 260 respondents among the three country samples, ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 49 publications
(55 reference statements)
1
52
0
Order By: Relevance
“…This is because it could provide wineries with competitive advantages as a result of cost reduction or product differentiation thanks to eco-labelling, for example, and through an improvement in the firm's reputation [26]. Consumers might consider products to be unique or innovative if they are produced in a sustainable and environmentally-friendly way [73]. Previous studies, however, reveal that the personal environmental values of those responsible are also important for environmental proactivity in this sector [22].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This is because it could provide wineries with competitive advantages as a result of cost reduction or product differentiation thanks to eco-labelling, for example, and through an improvement in the firm's reputation [26]. Consumers might consider products to be unique or innovative if they are produced in a sustainable and environmentally-friendly way [73]. Previous studies, however, reveal that the personal environmental values of those responsible are also important for environmental proactivity in this sector [22].…”
Section: Discussionmentioning
confidence: 93%
“…Unsurprisingly, other factors do exist that determine and explain the economic results of wineries, such as label and designation of origin [27]. The importance of these results stems from the fact that wineries have traditionally ignored environmental concerns which they consider to be irrelevant since this is not one of most polluting sectors [73]. There is, however, evidence to suggest that such an approach is wrong.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The literature shows that, although the perception of green and sustainable issues in wine differs among countries [42] and some industries are greener than others [35], consumers give importance to environmental attributes when purchasing wine [43]. Yet, it is important to underline that differences among countries depend on the degree of involvement of associations, institutions, policy-makers and the cultural approach to green issues [35,37]; this set of factors influences the entrepreneurial attitude towards green issues [38].…”
Section: Motivations and Driversmentioning
confidence: 99%
“…Research carried out in the field of the wine business has shown that a multiplicity of drivers coexist with the aim of promoting a sustainable orientation among wine business stakeholders [34][35][36][37][38].…”
Section: Motivations and Driversmentioning
confidence: 99%